Dampak Riyāḍah Al-Qur’an Terhadap Santri : (Studi Kasus Pada Pondok Pesantren Asshiddiqiyah II Batu Ceper Tangerang) - Fitriyani, Kurnia Nur; Ulinnuha, Muhammad (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
In the complex challenges of modern times, the building of strong character and integrity is a top priority in pesantren-based education. This research is inspired by people who have finished reciting the Qur'an but might not be very good at memorizing the Qur'an.riyadah Al-Qur’an is a form of effort to maintain memorization of the Qur'an. This study provides an in-depth understanding of the practice of the riyadah of the Qur'an. The formulation of the problem in this study is how the genealogy of the Qur'an riyadah at the Asshiddiqiyah II Islamic Boarding School, how the practice of the Qur'an riyadah at the Asshiddiqiyah II Islamic Boarding School, and the impact of the Qur'anic riyadah on students at the Asshiddiqiyah II Islamic Boarding School. Then in this study using descriptive qualitative research with field research, which is a study that utilizes data sources using interview results. Initially, the genealogy that occurred began with students who had read the Qur'an 30 juz so as not to waste their memorization. Therefore, in order for students to get used to continuing to read and maintain memorization of the Qur'an, riyadah activities of the Qur'an are held. The practice carried out in the riyadah activities of the Qur'an is carried out individually by staying focused on reading the Qur'an in one day one khataman for 41 days. Then there is the effect that occurs when the riyadah of the Qur'an on the students of Asshiddiqiyah II Islamic Boarding School is different for each recipient. This research shows that the riyadah of the Qur'an that took place in Pondok Asshiddiqiyah II was good. Because Asshiddiqiyah II Islamic Boarding School is a modern Islamic boarding school located in the middle of the capital city but can bring Sufism teachings in it.